Penerapan Metode Eksperimen untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPA - Katarina Surat Boli; Siti Arafat; Yohana Nono B.S (Journal of Elementary School (JOES), 2018)
The research aims at improving students science learning achievement with material "the characters of light" at grade V SDI Lewopao Central Adonara subdistrict East Flores Regency. It was a classroom action research. The result was that in cycle I, and II, there was score improvement in which ,the average score in cycle I was 62,03 with complete score 46,66%, and in cycle II was 88,33 with perfect result 100%. By the observation sheets during the teacing and learning activities the average score was 61,36% and in cycle II becae 90,90%. In summary, the application of experiment method can improve students science learning. Keywords: Experimental Method, Achievement, Science Subject.